Postpartum Pulmonary Embolism in a Patient With Fontan Circulation. (April 2015) - Pinto, Candida; Vettukattil, Joseph J.; Haw, Marcus P.
Pregnancy is typically not recommended in patients with Fontan circulation. Although patients are well aware of the risks for the mother and fetus, an increasing number opt to become pregnant. The higher rate of survival into adulthood post-Fontan procedure is a likely factor as a result of improved management of single ventricle anatomy. Postpartum thromboembolism is a known complication, but its prevalence and management are not clearly defined. We present a case of massive pulmonary embolism two weeks postpartum in a patient with double inlet left ventricle palliated with lateral tunnel Fontan.